Marital Rape in The Indian Legal Scenario - K Pattnaik, Prabir; Chakraborty, Nilanjan (International Journal of Psychosocial Rehabilitation, 2025)
Despite the increased recognition in India of various penal laws, in the past two to three decades, the Marital Rape has generated. A special law on marital rape is needed in India, which should also be accepted in this particular matter with international norms. Women have been given the right to fight for safety, but her own husband, whom she married with utter conviction, seeks to harm and torment her by having a powerful sex without her permission that eventually spoils. Unfortunately, in the context of the irrevocability of consent to matrimonial cohabitation, the husbands commit sexual violence. Society and legislature do not even consider such sexual violence by the husbands, which significantly impairs the status of women in society and maintains the status quo of the subjugated position of women in the family as well as in society